ANALISIS FUNDAMENTAL SAHAM DI SEKTOR ASURANSI ( Studi Kasus Di Bursa Efek Indonesia 2014-2017) - Wahyuningsih, Sri (P4M STIE Putra Bangsa, 2018)
This study aims to determine the prospect of growth and fair value of a stock by using fundamental analysis with EPS method (Earning Per Share and PER (Price To Earning Ratio) in determining an investment.The research method used is by using descriptive method with qualitative approach from the Report Annual Finance in 7 companies in the insurance sector. The result of this research is that the insurance sector experienced a fairly slow growth but still produce earnings.Experienced rankings of 7 companies in the insurance sector in 2018 quarter was ASRM of 283.95 medium the lowest PER level is ASDM of 5.15x. But if viewed from the market capitalization and the number of shares in circulation then the fair value is ASDM with the result then if you have to choose then that will be selected is a low PER with the number of shares outstanding smaller . The Per To Earning Ratio The ratio to PBV (Price Book Value) results in a decision to buy or sell stock prices. Keywords: Fundamental Analysis, PER and PBV